Using Crop Diversity to Adapt to Climate Change - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Summary video from a side event organized by the CCAFS project on Policy Support for Climate Resilient, Biodiversity-rich Seed Systems, led by Bioversity International, at the 8th Session of the Governing Body of the International Treaty on Plant Genetic Resources for Food and Agriculture.